Humberstone on Ayer’s Emotivism - Jeremiah Joven Joaquin (Organon F, 2023)
In The Connectives, Lloyd Humberstone offers an interpretation of A. J. Ayer’s emotivism using W. S. Cooper’s semantics for ordinary logic. In this discussion note, I argue that this proposed interpretation fails to stay true to Ayer’s view.